2009
DOI: 10.1128/aem.01331-08
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Wastewater Indicators and Human Pathogen Genomes in Biosolids Produced by Class A and Class B Stabilization Treatments

Abstract: Domestic sewage sludges that have been stabilized to reduce pathogen content are termed biosolids; their beneficial reuse for agricultural applications constitutes approximately 60% of the 7 million dry tons generated each year in the United States (6). Driven by health complaints from residents living near application sites, concern has been expressed that a hazardous exposure is created when biosolid aerosols are spread onto fields, incorporated into soils, and released during high-wind events (23,36). Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 44 publications
8
84
1
1
Order By: Relevance
“…Several studies have reported the occurrence of enteric viruses in biosolids (18,35,47); however, information on the quantity and infectivity of enteric viruses in biosolids is still limited, and most studies focused solely on enteroviruses (41). Few studies have reported the levels of human adenoviruses (HAdV) in biosolids (6,47), and no quantitative results have yet been reported on some of the emerging viruses, such as hepatitis A virus (HAV) and noroviruses (NV).…”
mentioning
confidence: 99%
“…Several studies have reported the occurrence of enteric viruses in biosolids (18,35,47); however, information on the quantity and infectivity of enteric viruses in biosolids is still limited, and most studies focused solely on enteroviruses (41). Few studies have reported the levels of human adenoviruses (HAdV) in biosolids (6,47), and no quantitative results have yet been reported on some of the emerging viruses, such as hepatitis A virus (HAV) and noroviruses (NV).…”
mentioning
confidence: 99%
“…However, Viau and Peccia (2009) detected Legionella pneumophila, S. aureus and C. difficile in biosolids generated from 29 STPs in USA which was treated with mesophilic, temperaturephase anaerobic digestion and composting process, which Table 4 Processes to significantly reduce pathogens (PSRPs). Source; US EPA (2003) Treatment process Procedure of the treatment process Composting Using either the within-vessel, static aerated pile, or windrow composting methods, the temperature of the sewage sludge is raised to 40 °C (104 °F) or higher and remains at 40 °C or higher for 5 days.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…In the light of the aforementioned, Enerhall and Stenmark (2012) also reported that TC and enterococci were 5.8 and 5.08 log 10 CFU/100 mL, respectively in treated sewage generated from STP in Sweden, which used filtration system during the disinfection process. Viau and Peccia (2009) stated that the concentrations of FC in biosolids generated from 29 STPs in USA, which use mesophilic anaerobic digestion (MAD), temperature-phased anaerobic digestion (TPAD), composting the biosolids after anaerobic digestion (COM) corresponded to US EPA regulatory limits for each biosolids Class A and Class B.…”
Section: Current Status Of Sewage Treatment In Middle East Countriesmentioning
confidence: 99%
“…For example, viruses can survive the composting process when certain zones of the heap are not exposed or exposed for too short times to the temperatures required for viral inactivation. Average concentrations and reductions of a variety of enteric pathogens in biosolids by composting (COM) and temperature-phased anaerobic digestion (TPAD) for Class A and mesophilic anaerobic digestion (MAD) for Class B biosolids as well as the annual log probability of viral infections associated with land applications and aerosols were examined in detailed reviews by Viau et al (Viau et al, 2011;Viau and Peccia, 2009). Values for viability and molecular-based determinations were compared.…”
Section: Biosolidsmentioning
confidence: 99%